Rhinolith in a 37-year-old lady: a case report of an unusual presentation - Anuar, Khairullah Bin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Rhinoliths are uncommon nasal masses. They are mineralized masses found within the nasal cavity. Their clinical presentation can be varied. We presented a 37-year-old lady with previous history of lymphoma presented with 6 months history of left sided nasal blockage associated with purulent nasal discharge and cacosmia. Rigid nasoendoscopy showed irregular hard mass along the floor of nasal cavity. Computed tomography (CT) scan was performed and showed left intranasal mass with calcification. Subsequently the rhinolith was removed endoscopically under general anesthesia. Unusual foreign body was found within the rhinolith. Following the removal, she had uneventful recovery. This case has to be treated carefully as with previous history of lymphoma it might suggest recurrence. However, it also illustrates the importance of rigid nasoendoscopy and the radiological assessment in establishing the diagnosis and management of rhinolith.